Effects of internal recycling time mode and hydraulic retention time on biological nitrogen and phosphorus removal in a sequencing anoxic/anaerobic membrane bioreactor process - Song, Kyung-Guen; Cho, Jinwoo; Ahn, Kyu-Hong (SPRINGER, 2009)
This study investigated the effects of internal recycling time mode and hydraulic retention time (HRT) on nutrient removal in the sequencing anoxic/anaerobic membrane bioreactor process. Denitrification and phosphorus release were reciprocally dependent on the anoxic/anaerobic time ratio (Ax/An). As Ax/An increased, nitrogen removal rate increased but phosphorus removal rate decreased. The increasing Ax/An provided the longer denitrification period so that the organic substrate were consumed more for denitrification rather than phosphorus release in the limited condition of readily biodegradable substrate. Decreasing HRT increased both nitrogen and phosphorus removal efficiency because as HRT decreased, food-to-microorganism loading ratio increased and thus enhanced the biological capacity and activity of denitrifying bacteria. This could be verified from the observation mixed liquor suspended solids concentration and specific denitrification rate. The change of Ax/An and HRT affected phosphorus removal more than nitrogen removal due to the limitation of favourable carbon source for phosphorus accumulating organisms.
Keywords: WASTE-WATER TREATMENT; ACTIVATED-SLUDGE; NUTRIENT; NITRATE; SYSTEM; SCALE